Penggunaan Daun Sambiloto Untuk Pharyngitis - Susilo Yulianto (Jurnal Kebidanan dan Kesehatan Tradisional, 2017)
Abstract: The Knowledge Society, Tamarind, Cough. Cough is one of the body's defense mechanisms, especially respiratory should be managed properly. Coughmechanism depends on five components: cough receptors, afferent nerve center, cough, nerve efferent, and effector. Based on preliminary studies conducted by the authors obtained the data that the knowledge society is very diverse Bakung village. The purpose of this study to determine the knowledge society Bakung village, Jogonalan, Klaten of tamarind to cough. This research is descriptive quantitative research with cross sectional approach. The sampling technique using a quota sampling with 30 respondents. Data collection instruments used were questionnaires knowledge of tamarind. Data was analyzed by descriptive analysis. Results of analysis of the data showed that respondents who have a good knowledge of a number of 27 respondents (90%), while respondents who have sufficient knowledge of three respondents (10%). The conclusion of this study that people's knowledge of tamarind to cough, with both categories (90%), and knowledge of the category enough (10%).